Tokyo 2026 - Goss, Rob; Fong, Cherise; Fong, Todd; Joe, Melinda; Kahan, Kim; Kittaka, Louise George; Okazaki, Manami; Tan, Winnie (Travel writer) (Lonely Planet, 2026)
Discover Tokyo's most popular experiences and best kept secrets from wandering the maze-like streets of Shimo-Kitazawa for atmospheric cafes and artistic hideaways; to watching belly-slapping sumo wrestlers at Ryogoku Kokugikan in January, May and September; and eating your fill of yakitori fresh off the grill at Omoide Yokocho.